Clinical Significance of Protein Expression of Cyclooxygenase-2 and Somatostatin Receptors in Gastroenteropancreatic Neuroendocrine Tumors - Kim, Hee Sung; Lee, Hye Seung; Kim, Woo Ho (Cancer research and treatment, 2011)
This study was undertaken to evaluate the significance of cyclooxygenase-2 (COX2) overexpression and the expression of somatostatin receptor (SSTR) subtypes in gastroenteropancreatic neuroendocrine tumors (GEP-NETs). Two hundred and forty-seven cases of GEP-NET, comprising 86 foregut and 156 hindgut primary NETs, and 5 metastatic NETs in the liver, were studied retrospectively with immunohistochemistry for COX2, chromogranin A, Ki-67, SSTR1, SSTR2, and SSTR5. COX2 overexpression was observed in 54%(126 of 234), and SSTR1, SSTR2, and SSTR5 positivity in 84%(196 of 233), 72%(168 of 233), and 55%(128 of 232), respectively. COX2 overexpression was found to be positively correlated with Ki-67 labeling index and inversely correlated with the expression of SSTR subtypes. In addition, the expression of SSTR subtypes was tightly correlated in any comparative pairs. A significant inverse correlation was found between COX2 and SSTR2 expression in the foregut, but not hindgut NETs. Kaplan-Meier analyses showed that COX2 overexpression (p=0.003) and high Ki-67 labeling index (p<0.001) were associated with poor overall survival (OS), whereas expression of SSTR2 (p<0.001) was associated with better OS of GEP-NET patients. Multivariate analysis revealed negative SSTR2 expression as an independent prognostic marker in GEP-NET patients (p<0.001). Our results suggest that expression of SSTR subtypes is associated with favorable prognosis, whereas COX2 overexpression is associated with poor prognosis in GEP-NETs. Taken together, COX2 could be a possible therapeutic target in some subsets of GEP-NETs.